Discovering the meaningfulness of art in organizations: Experiences with Add Art Hamburg 2015 - Ariane Berthoin Antal; Ilana Nussbaum Bitran (Zeitschrift für Kulturmanagement, 2018)
Given the growth in corporate art collecting, surprisingly little research has been conducted on how employees experience art in the workplace. This article draws on survey data collected in the context of add art Hamburg 2015, which included permanent and temporary exhibitions in 22 organizations. The findings confirm that the presence of artworks can interrupt routine ways of perceiving and using space. It triggers questions and conversations, which stimulate sensemaking processes and enrich relationships with colleagues. It also opens managers and employees to seeing everyday life and relationships with customers in a more holistic way. Furthermore, the study shows that the removal of artworks is experienced as loss and emptiness, as well as a harbinger of new potential. Finding that employees welcome more art at work, the article discusses the conditions under which people in organizations can engage with the arts as co-learners.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; corporate art collection; art exhibition; artistic intervention; arts and business; add art